Komedi dalam Q.S An-Najm 43: Studi Analisis Penafsiran (Tafsir Lisan) Quraish Shihab dalam Channel Youtube Najwa Shihab - Ananda Rizki Prianka Putri; Andina La'aliy Rohmati Robbina; Annisa Rahmi Faiziah; Dian Sri Lestari (Canonia Religia, 2024)
This article examines Quraish Shihab's views on comedy from an Islamic perspective, which he attributes to Q.S. An-Najm: 43 through an analysis of video uploads on Najwa Shihab's YouTube channel. Through a descriptive-analytical approach, this research utilizes Walter J. Ong's theory of linguistics to analyze the characteristics of linguistics in the delivery of Quraish Shihab's oral interpretations. The results show that the reality of comedy is currently allowed in Islam as long as it is not excessive and does not violate religious norms. Oral interpretations presented through YouTube social media have advantages such as broader accessibility and relevance to everyday life. However, it also has disadvantages, such as the lack of direct interaction and the potential for misperception. This study emphasizes adapting the oral tradition in the digital era that can reach a wide audience and guide the community to understand comedy wisely according to Islamic values. This study is expected to be a contribution to contemporary tafsir studies and an evaluation in the use of digital media as a means of da'wah and delivery of Qur'anic studies.